A physicochemical method for increasing methane production from rice straw: Extrusion combined with alkali pretreatment. (15th December 2015) - Zhang, Yalei; Chen, Xiaohua; Gu, Yu; Zhou, Xuefei
Graphical abstract: Highlights: The first report of using extrusion combined with NaOH pretreatment for methane production from LB. Pretreatment with an ALR of 3.0% at 35 °C for 48 h increased methane production from rice straw by 54%. The ER efficiency improved from 38.9% to 59.9% using extrusion combined with NaOH pretreatment. The changes in the physicochemical characterization of rice straw were investigated. Abstract: Pretreatment is a crucial processing step in the conversion of lignocellulosic biomass (LB) into methane by anaerobic digestion. A physicochemical LB pretreatment method, i.e., using an extruder to reduce the biomass size prior to sodium hydroxide (NaOH) pretreatment, was reported. The optimal condition for economic feasibility and pretreatment efficiency was an alkaline loading rate of 3.0% at 35 °C for 48 h. Under this condition, the methane production from the rice straw that was processed by extrusion combined with NaOH pretreatment was 54.0% higher than that of a control sample. The energy recovery (ER) efficiency improved from 38.9% to 59.9% using the combination pretreatment. The mechanisms that caused the significant improvement in the methane production and ER efficiency in the extrusion–NaOH pretreatment were investigated. The pretreatment changed the physical properties (water-holding capacity, specific porosity, specific surface area and crystallinity index), the chemical composition (lignin, benzene–ethanol extractives and hot-water extractives) and the chemical structure, which increased degradation of holocelluloses and other difficulty biodegradable compounds.